Feature Story: Indigenous Research Showcase Week brings the TRC Calls to Action to life - External Relations, University of Regina (External Relations, University of Regina, 2018)
The University of Regina’s annual Indigenous Research Showcase Week is a celebration of diversity, innovation, and connections to community. The week-long event is also another way in which the University is acting on the Calls to Action laid out in the Truth and Reconciliation Commission’s (TRC) Final Report – helping to make concrete changes in society, redressing the legacy of residential schools and advancing the process of Canadian reconciliation. Staff no